The Architectural Decoration of Altar Spaces in the Roman Churches of the 12th–13th Centuries - Kuznetsova, Nataliya S. (Actual Problems of Theory and History of Art, 2019)
Altar zone is the most significant and sacred part of the interior of any Christian church. Architects and sculptors used special methods to decorate an altar and to emphasize its particular role in the composition of the building. Rome was an important and celebrated center for pilgrims who wished to venerate innumerous relics and get blessing of the Pope. The article analyzes the architectural decoration of altar zone in the churches of Rome. It included an altar itself, an altar barrier, a pulpit and a ciborium. There are a few monuments that can be explored as examples of a typical medieval arrangement of the altar space in Rome: San Giorgio in Velabro, Santa Maria in Castello in Tarquinia, Santa Maria Assunta in Anagni and Santi Giovanni e Paolo in Ferentino. These monuments represent the first type of the alter space arrangement.Santa Maria in Cosmedin and San Clemente are the examples of second type, more severe and secluded. So, it is possible to identify several methods of creating altar spaces and to characterize particular features of style and iconography of the Roman medieval architecture in general and of altar spaces in particular.
Keywords: altar space; Rome; architecture; decoration